STRENGTH-WEAKNESS-OPPORTUNITY-THREATS (SWOT) ANALYSIS OF EXTRAORDINARY LEGAL EFFORTS, EXECUTIONS, AND EXAMINATIONS IN ADDRESSING THE CORRUPTION CHALLENGES IN INDONESIA - Henry D.P. Sinaga (Journal of Governance and Administrative Issues, 2022)
One of the great expectations for dealing with the challenge of corruption in Indonesia is to strengthen the role of Extraordinary, Execution and Examination Legal Remedies, which are the (legal) structure of the Attorney General's Office. Based on a literature review using the Strength-Weakness-Opportunity-Threats (SWOT) Analysis, it can be concluded that revitalizing the Extraordinary Legal Remedies, Execution, and Examination sections can improve the optimization of the Attorney's performance in dealing with corruption in Indonesia. This revitalization is based on a SWOT analysis which shows that there are still weaknesses and threats, both internally and externally, at the Attorney General's Office. It is necessary to consider the existence of sub-monitoring and evaluation, as well as sub-reporting and analysis to strengthen the duties and functions of Extraordinary Legal Remedies, Execution, and Examination to minimize existing weaknesses and threats.